O responder relacional: elaboração e aplicação de uma programação de ensino de comparação em História - Fonseca, Cíntia Cássia (2020)
In the teaching of History, the exercise of comparison corresponds to an essential repertoire for the understanding of historical processes and for the identification of the permanences and ruptures between the present and the past. In this sense, it is necessary to teach the student to think and comparison is essential for the individual to establish relationships between ideas. Relational Frame Theory (RFT) highlights the importance of teaching relational networks for cognitive development and provides information for training these skills. This study aims to present a proposal for comparative teaching in History, in software format www.mindtrain.com.br that resulted in 340 activities with stimuli of figures and texts. The study included 10 children, aged 8 and 11, who attended different grades, in private schools in the city of São Paulo. The following materials were used: printed texts, pens and pencils, bond paper, computers and cell phones. The research was applied individually and remotely. The participants carried out the initial repertoire evaluations, the comparison programmed instruction, the partial evaluations and the final repertoire evaluation. The Pre-Test and Post-Test data were collected through a written activity on the comparison of two History events. For data analysis, we considered the number of compared aspects, 15 similarities and 11 differences, both in the Pre-Test and in the Post-Test. Among the results, it was found that, after training, the group average increased from five to nine comparison aspects; there was a positive change for nine participants; the mentions of similarities was superior to differences; the repertoire of differences proved to be more complex to be issued; a very varied repertoire of participants was identified. New directions for the teaching of comparison in future studies are suggested